Atypical clinical manifestation and protracted latency are observed in the emerging variant of checkpoint inhibitor‐associated bullous pemphigoid. (30th September 2022) - Kridin, Khalaf; Hammers, Christoph M.
Abstract : Linked Article: Kawsar et al. Br J Dermatol 2022; 187:981–987 .